A distal centriolar protein network controls organelle maturation and asymmetry - Lei Wang (Nature Portfolio, 2018)
Removal of daughter centriole-specific/enriched proteins (DCPs) and assembly of distal appendages (DA) are important for centrosome asymmetry. Here, the authors report that a centriolar distal end protein network regulates DCP removal, DA assembly, and ciliary vesicle docking.